2019
DOI: 10.1007/s10803-019-04224-5
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Motor Skill Acquisition for Bicycle Riding in Children with ASD: A Pilot Study

Abstract: Motor impairment is common in autism spectrum disorder (ASD) and, as such, a potential target for interventions to improve adaptive functioning. This study investigated motor skill acquisition in children with ASD (n = 15, 12 males; ages 7 -16 years) during iCan Bike Camp, a one-week, community-based intervention (5×75-minute sessions) to teach independent bicycle riding. After completing the camp's task-oriented, individualized training program, all participants demonstrated motor skill acquisition on the bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Using the ROBINS‐I tool 30 for the four non‐randomized studies, 42,43,47,48 the overall risk of bias was identified as ‘critical’ for one interrupted time series study 42 and ‘serious’ for three studies 43,47,48 (Figure S4). Outcome data were reported for all participants in all four studies 42,43,47,48 . In the two interrupted time series studies, 42,43 determination of ‘serious’ risk of bias was related to lack of blinding of the outcome assessors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the ROBINS‐I tool 30 for the four non‐randomized studies, 42,43,47,48 the overall risk of bias was identified as ‘critical’ for one interrupted time series study 42 and ‘serious’ for three studies 43,47,48 (Figure S4). Outcome data were reported for all participants in all four studies 42,43,47,48 . In the two interrupted time series studies, 42,43 determination of ‘serious’ risk of bias was related to lack of blinding of the outcome assessors.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported outcomes at the body structures and functions level, 39,40,42,44,47 including strength, height, weight, body mass index, cardiorespiratory fitness, balance, gait quality, and locomotor endurance. Ten studies reported activity‐level outcomes, 39–48 including gross motor function, physical activity, sit‐to‐stand capacity, learning to ride a standard two‐wheel bicycle, locomotor performance, and peak cycling power output. Two studies reported participation‐related outcomes: 41,47 participation in life activities and mean level of enjoyment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory-motor outcomes for Study 1 and Study 2 were selected to assess balance, strength, sensory processing, and motor coordination. These postural components were selected based on research that supports the importance of motor skill development as contributing to success in bicycle riding, citing strength, balance, coordination and endurance [ 6 , 16 , 17 ]. These activities were subtests from the Sensory Processing Three Dimensions (SP3D) Measure [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, it is a natural and common physical exercise. It has been proven feasible to teach children with ASD to ride a bicycle, and cycling has been shown to increase children’s physical exercise levels and improve their social behavior (23,24). Importantly, learning to ride a bicycle is physically and cognitively demanding, and it aligns with the cognitive stimulation hypothesis proposed by Best (25) and Pesce (26).…”
mentioning
confidence: 99%